Psychoeducational Interventions on Conflict Resolution Styles among Individuals Involved in Commuter Marriages - Qurrata A'yun; Theresia Indira Shanti (Journal of Innovation and Community Engagement, 2021)
Couples in commuter marriages who live apart face many challenges, such as having ineffective communications which lead to conflict. Couples who use a positive and constructive conflict resolution style, have a better chance of getting a better quality of marital life. This intervention aims to provide psychoeducation to participants in order to understand conflict resolution styles that can be applied when dealing with and resolving conflicts in commuter marriages. The evaluation of the intervention effect was carried out by comparing the knowledge and skill to the application of conflict resolution styles, before and after the intervention. After being given psychoeducation, it was found that 25 participants changed the resolution style they would use when experiencing conflict with their partner. While the other 5 participants still chose the same resolution style. In conclusion, through this psychoeducation, participants have new knowledge about various resolution styles that can be used, and according to the conflict conditions experienced by each partner.